The Prevalence of Generalised Anxiety Disorder Among Prisoners of the Penitentiary Institution in North-Eastern Poland - Stawinska-Witoszynska, Barbara; Czechowska, Katarzyna; Moryson, Waclaw; Wieckowska, Barbara (Frontiers in Psychiatry, 2021)
Generalised anxiety disorder (GAD) is one of the most common mental disorders. The psychosocial factors that may lead to GAD include stress, traumatic events, conscious and unconscious internal conflicts, and low social and economic status. Imprisonment and forced isolation may favour the development of depression or anxiety disorders in inmates. Thus, this study aimed to analyse the prevalence of GAD in the population of inmates detained in one of the largest penitentiary units in Poland. The data comes from 2017 and includes information on 635 male inmates incarcerated at the Czerwony Bór Prison. The information comes from the health records of individual inmates, kept by the prison outpatient clinician, and documented consultations with doctors of units outside the prison. The classification of GAD (F41.1) was made in accordance with the 10th Revision of the International Statistical Classification of Diseases and Health Problems and the clinical diagnosis made by a psychiatrist. The Mann-Whitney test was used to compare quantitative data without normal distribution, chi-squared test or Fisher exact test for comparing qualitative data. A one-dimensional and multi-dimensional logistic regression model was used to examine the impact of the prison type on the prevalence of GAD. Generalised anxiety disorder was observed among 44 prisoners (6.9%), most often in the age range 30-39 years and among men younger than 30 years, respectively 40.9% and 31.8% of all diagnosed. The average age of patients was 34.6 years. The least number of prisoners with GAD was in the age group 50-59 (2.3%). Nearly 66% of patients were prisoners detained in a closed type prison; the chance of GAD was three times higher than among the prisoners in a half-open and open type facility. Generalised anxiety disorder was diagnosed significantly more often with those currently serving a prison sentence than those before incarceration. In Polish conditions, the importance of the problem associated with GAD is evidenced by a significant increase in its prevalence in the prison environment and a three times higher chance of developing GAD among prisoners in a closed type institution, which calls for highly organised psychiatric care and increased availability of psychological assistance.